2019
DOI: 10.1103/physrevb.100.144412
|View full text |Cite
|
Sign up to set email alerts
|

Weak ferromagnetism in hexagonal Mn3Z alloys (Z=Sn,Ge,Ga)

Abstract: We present combined spin model and first principles electronic structure calculations to study the weak ferromagnetism in bulk Mn 3 Z (Z=Sn, Ge, Ga) compounds. The spin model parameters were determined from a spin-cluster expansion technique based on the relativistic disordered local moment formalism implemented in the screened Korringa-Kohn-Rostoker method. We describe the magnetic ground state of the system within a three-sublattice model and investigate the formation of the weak ferromagnetic states in term… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Naturally, it is of interest to understand how such a large AHE can occur in an antiferromagnet, and there has been a spate of theoretical studies [2,[10][11][12][13][14][15][16][17][18]. The symmetries of noncollinear antiferromagnets generically do not forbid the AHE, and several of the recent studies have concluded that the particular chiral pattern of Mn spins can lead to large Berry curvature at the Fermi surface and thus a large AHE, as predicted by an earlier work [19].…”
mentioning
confidence: 85%
“…Naturally, it is of interest to understand how such a large AHE can occur in an antiferromagnet, and there has been a spate of theoretical studies [2,[10][11][12][13][14][15][16][17][18]. The symmetries of noncollinear antiferromagnets generically do not forbid the AHE, and several of the recent studies have concluded that the particular chiral pattern of Mn spins can lead to large Berry curvature at the Fermi surface and thus a large AHE, as predicted by an earlier work [19].…”
mentioning
confidence: 85%
“…Recently, thin-films with different thickness ranging from 1 nm to 5 nm of both these materials have been grown using UHV magnetron sputtering [88][89][90][91]. In addition, different values of damping constants have been reported for Mn 3 Sn [56,77]. Therefore, we expect the results presented in Sections III C, IV and V to be useful for benchmarking THz dynamics in experimental set-ups with such thin films metallic antiferromagnets.…”
Section: Discussionmentioning
confidence: 99%
“…We then used the Spin-Cluster Expansion ( ) to extract spin model parameters from the state by mapping the adiabatic energy surface of the fluctuating state onto a Heisenberg model [17,18]. This method has been used successfully to describe -interfaces such as exchange bias systems [18,19], as well as bulk noncollinear antiferromagnets [20,21].…”
Section: A Self-consistent Calculationsmentioning
confidence: 99%